Effect of nifedipine on exercise tolerance in angina pectoris. Issue 3 (September 1980) - McIlwraith, G R; Kidner, P H; Oram, S
Abstract : Nifedipine is a new antianginal drug, the calcium-antagonistic inhibitory action on excitation-contraction coupling apparently being so pronounced that, in therapeutic dosage, all other pharmacological properties are negligible. Its effect on exercise tolerance in angina was assessed by an exercise study involving 14 patients: single-stage exercise tests were chosen and the advantages of this are given. Our results suggest that the onset of action occurs after about 20 minutes, reaches a peak of activity at approximately one-half to two hours, and some effect may still be present at three hours. There was a significant improvement in exercise times with a mean rise of 50 per cent over placebo.